Binding properties of the quaternary assembly protein SPAG1. Issue 11 (14th June 2019) - Chagot, Marie-Eve; Dos Santos Morais, Raphael; Dermouche, Sana; Lefebvre, Dorian; Manival, Xavier; Chipot, Christophe; Dehez, François; Quinternet, Marc
Abstract : In cells, many constituents are able to assemble resulting in large macromolecular machineries possessing very specific biological and physiological functions, e.g. ribosome, spliceosome and proteasome. Assembly of such entities is commonly mediated by transient protein factors. SPAG1 is a multidomain protein, known to participate in the assembly of both the inner and outer dynein arms. These arms are required for the function of sensitive and motile cells. Together with RUVBL1, RUVBL2 and PIH1D2, SPAG1 is a key element of R2SP, a protein complex assisting the quaternary assembly of specific protein clients in a tissue-specific manner and associating with heat shock proteins (HSPs) and regulators. In this study, we have investigated the role of TPR domains of SPAG1 in the recruitment of HSP chaperones by combining biochemical assays, ITC, NMR spectroscopy and molecular dynamics (MD) simulations. First, we propose that only two, out of the three TPR domains, are able to recruit the protein chaperones HSP70 and HSP90. We then focused on one of these TPR domains and elucidated its 3D structure using NMR spectroscopy. Relying on an NMR-driven docking approach and MD simulations, we deciphered its binding interface with the C-terminal tails of both HSP70 and HSP90. Finally, we addressed the biological function of SPAG1 and specifically demonstrated that a SPAG1 sub-fragment, containing a putative P-loop motif, cannot efficiently bind and hydrolyze GTP in vitro . Our data challenge the interpretation of SPAG1 possessing GTPase activity. We propose instead that SPAG1 regulates nucleotide hydrolysis activity of the HSP and RUVBL1/2 partners.